Biweekly carboplatin/gemcitabine in patients with advanced urothelial cancer who are unfit for cisplatin-based chemotherapy: Report of efficacy, quality of life and geriatric assessment - Bamias, A.; Lainakis, G.; Kastritis, E.; Antoniou, N.; Alivizatos, G.; Koureas, A.; Chrisofos, M.; Skolarikos, A.; Karayiotis, E.; Dimopoulos, M.A. (Oncology, 2007)
Objective: We evaluated safety and efficacy of first-line gemcitabine/carboplatin in unfit-for-cisplatin patients with advanced urothelial carcinoma and the effect on the quality of life and functional status of elderly patients (aged >70). Methods: Unfit patients had ECOG performance status (PS) ≥2, creatinine clearance <50 ml/min or comorbidities precluding cisplatin administration. Carboplatin at area under the curve of 2.5 and gemcitabine 1,250 mg/m2 were administered biweekly. Elderly patients were stratified into group 1 (no activities of daily living (ADL) or instrumental ADL dependency and no comorbidities), group 2 (instrumental ADL dependency or 1-2 comorbidities) and group 3 (ADL dependency or ≥2 comorbidities). Results: Thirty-four patients were enrolled: 68% had PS 2-3, 69% a creatinine clearance <50 ml/min and 65% had 1 or more comorbidities. There were 3 cases of grade 3 toxicity (9%). Response rate was 24% [95% confidence interval (CI) 11-41]. Median follow-up was 8 months, median progression-free survival 4.4 months (95% CI 1.03-7.75) and median overall survival 9.8 months (95% CI 4.7-14.9). Patients in geriatric assessment groups 1 and 2 had a significantly longer median progression-free survival compared to group 3 [6.9 months (95% CI 1.3-12.4) vs. 1.9 months (95% CI 0.5-3.2); p = 0.005]. Conclusion: First-line gemcitabine/carboplatin combination is active in unfit-for-cisplatin patients with advanced urothelial carcinoma. Pretreatment quality of life and geriatric assessment may be useful in selecting patients likely to benefit from this treatment. Copyright © 2008 S. Karger AG.
Keywords: Elderly; Gemcitabine; Unfit; urothelial cancer